2021
DOI: 10.1371/journal.pone.0259474
|View full text |Cite
|
Sign up to set email alerts
|

Mobile interventions targeting common mental disorders among pregnant and postpartum women: An equity-focused systematic review

Abstract: Introduction Pregnant and postpartum women face major psychological stressors that put them at higher risk of developing common mental disorders, such as depression and anxiety. Yet, their limited access to and uptake of traditional mental health care is inequitable, especially during the COVID-19 pandemic. Mobile interventions emerged as a potential solution to this discontinued healthcare access, but more knowledge is needed about their effectiveness and impact on health equity. This equity-focused systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
(92 reference statements)
0
15
0
1
Order By: Relevance
“…Health: Six (n = 6) included papers were within the domain of health (Banati & Idele, 2021; Das et al, 2021; Davic et al, 2021; Figueroa, Luo, Aguilera, & Lyles, 2021; Ray et al, 2021; Saad et al, 2021; Steinert, Alacevich, Steele, Hennegan, & Yakubovich, 2021)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health: Six (n = 6) included papers were within the domain of health (Banati & Idele, 2021; Das et al, 2021; Davic et al, 2021; Figueroa, Luo, Aguilera, & Lyles, 2021; Ray et al, 2021; Saad et al, 2021; Steinert, Alacevich, Steele, Hennegan, & Yakubovich, 2021)…”
Section: Resultsmentioning
confidence: 99%
“…Reviews: Seven (n = 7) included papers were reviews (Andermann et al, 2021; Banati & Idele, 2021; Bray & McLemore, 2021; Perri et al, 2021; Saad et al, 2021; Steinert et al, 2021) (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, women of a reproductive age often encounter their own unique challenges, and assessments should also factor in refugee lived experiences of pregnancy, childbirth, and raising children [ 21 ]. A recent review of mobile applications for women during pregnancy showed that technology-assisted approaches may improve timely access to mental health support and facilitate successful mental health care across different ethnicities [ 122 ]. Assessment tools for children may also need to include a broader spectrum of conditions and assess social determinants of health, developmental delays, family separation, and trauma [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine and web-based interventions may offer a promising alternative for perinatal patients in terms of flexibility, efficiency, and cost, potentially increasing the accessibility and scalability of treatment ( 28 ). Remote psychotherapy can also be offered in patient-centered settings and schedules (i.e., at home and during weekends), while practical barriers (i.e., wait times and costs for parking or transportation) can be minimized, including for perinatal populations ( 29 ). There nonetheless remain questions that are critical to examine from a health equity lens.…”
Section: Introductionmentioning
confidence: 99%